HLA/MHC and KIR characterization in humans and non‐human primates using Oxford Nanopore Technologies and Pacific Biosciences sequencing platforms. (9th January 2023) - Bruijnesteijn, Jesse
Abstract : The gene products of the HLA/MHC and KIR multigene families are important modulators of the immune system and are associated with health and disease. Characterization of the genes encoding these receptors has been integrated into different biomedical applications, including transplantation and reproduction biology, immune therapies and in fundamental research into disease susceptibility or resistance. Conventional short‐read sequencing strategies have shown their value in high throughput typing, but are insufficient to uncover the entire complexity of the highly polymorphic HLA/MHC and KIR gene systems. The implementation of single‐molecule and real‐time sequencing platforms, offered by Pacific Biosciences (PacBio) and Oxford Nanopore Technologies (ONT), revolutionized the fields of genomics and transcriptomics. Using fundamentally distinct principles, these platforms generate long‐read data that can unwire the plasticity of the HLA/MHC and KIR genes, including high‐resolution characterization of genes, alleles, phased haplotypes, transcription levels and epigenetics modification patterns. These insights might have profound clinical relevance, such as improved matching of donors and patients in clinical transplantation, but could also lift disease association studies to a higher level. Even more, a comprehensive characterization may refine animal models in preclinical studies. In this review, the different HLA/MHC and KIR characterization approaches using PacBio and ONT platforms are described and discussed.